2021
DOI: 10.3390/rs13050983
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Broadband Permittivity Determination Due to Liquid Surface Distortions in Semi-Open Test Cell

Abstract: We study how surface distortions of liquid samples due to a meniscus and a tilt of a semi-open coaxial test cell affect errors in a broadband permittivity determination. The study is based on the scattering parameters, obtained using the electromagnetic simulations of samples with flat and distorted surfaces in a broad frequency range up to 18 GHz. The parameters are processed with the classic Nicolson–Ross–Weir (NRW) method and our new meniscus removal technique. We analyze the errors for several samples of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Therefore, depending on the needs, the port 1 calibration plane can be at the top or bottom of the additional waveguide. The waveguide is integrated with a stand assuring vertical orientation crucial for reducing the effects of the higher modes, which was analyzed in our previous work [ 32 ].…”
Section: Design Of the Rectangular Waveguide Fixturementioning
confidence: 99%
“…Therefore, depending on the needs, the port 1 calibration plane can be at the top or bottom of the additional waveguide. The waveguide is integrated with a stand assuring vertical orientation crucial for reducing the effects of the higher modes, which was analyzed in our previous work [ 32 ].…”
Section: Design Of the Rectangular Waveguide Fixturementioning
confidence: 99%
“…The next paper "Errors in Broadband Permittivity Determination due to Liquid Surface Distortions in Semi-Open Test Cell" [9]…”
Section: Overview Of the Papers Published In The Special Issuementioning
confidence: 99%
“…In Section 2 , we present the model for a sample measurement and the algorithm for determining the permittivity (with detailed descriptions of solving the final equation in Appendix A ). We validate the new method in Section 3 by comparing the results with available reference data and with outcomes of our previously published meniscus removal method [ 33 , 34 ] obtained for propan-2-ol (IPA), a 50% aqueous solution of IPA and distilled water. Then, we summarize the work in the conclusion ( Section 4 ).…”
Section: Introductionmentioning
confidence: 97%
“…Errors in the extraction of the liquid permittivity caused by the upper-surface sample deformations have already been studied by authors who showed in [ 33 ] that the errors can be kept small, providing the cell axis is vertically oriented and the meniscus is reproducible at each cell state. For such an instance, we introduced a new approach to broadband permittivity extraction [ 34 ], called the meniscus removal (MR) method, since it is capable of removing the meniscus effect using the scattering matrices measured with a calibrated VNA on a semi-open coaxial test cell in just three states.…”
Section: Introductionmentioning
confidence: 99%